2017
DOI: 10.1089/mdr.2015.0279
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Beliefs Regarding Antimicrobial Therapy and Resistance Among Physicians in Alexandria University Teaching Hospitals and the Associated Prescription Habits

Abstract: Irresponsible prescription of antimicrobials (AMs) is the driving factor for the growing antimicrobial resistance (AMR) crisis. In this study, we assessed the knowledge, attitudes, perceptions, and beliefs regarding AMs and AMR together with the prescription habits of physicians in three University hospitals in Alexandria, Egypt. A 40-question survey was used. Physicians were stratified into residents and practicing staff members, and further into various departments. Clinical pharmacists at the University mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
31
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 9 publications
2
31
1
Order By: Relevance
“…The systematic search resulted in a total of 384 papers, with 345 papers left after removing duplicates, and 28 relevant papers upon reviewing titles and abstracts. Of these, 15 articles fulfilled our inclusion criteria upon full‐text review (Figure ), according to the United Nations, World Economic Situation and Prospects: four from Africa (two from East Africa: Ethiopia, the Democratic Republic of Congo, one from North Africa: Egypt and one from West Africa: The Gambia); nine from Asia (three from East Asia: Lao People's Democratic Republic, Malaysia, four from South Asia: Bangladesh, India and two from Western Asia: Saudi Arabia); and two from Latin America and the Caribbean (one from the Caribbean: West Indies and one from South America: Peru). All the studies were cross‐sectional, 13 were quantitative studies using questionnaires, and two were qualitative studies.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The systematic search resulted in a total of 384 papers, with 345 papers left after removing duplicates, and 28 relevant papers upon reviewing titles and abstracts. Of these, 15 articles fulfilled our inclusion criteria upon full‐text review (Figure ), according to the United Nations, World Economic Situation and Prospects: four from Africa (two from East Africa: Ethiopia, the Democratic Republic of Congo, one from North Africa: Egypt and one from West Africa: The Gambia); nine from Asia (three from East Asia: Lao People's Democratic Republic, Malaysia, four from South Asia: Bangladesh, India and two from Western Asia: Saudi Arabia); and two from Latin America and the Caribbean (one from the Caribbean: West Indies and one from South America: Peru). All the studies were cross‐sectional, 13 were quantitative studies using questionnaires, and two were qualitative studies.…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies reported on participants’ awareness and knowledge on antibiotics . Reported knowledge on antibiotics was either based on correct answers to questions that assessed participants’ knowledge or based on self‐assessment.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations